Increasing the efficiency of business process through authentic leaders and follower's attitude. Issue 2 (11th February 2021) - Malik, Muhammad Faisal; Khan, Muhammad Asif; Mahmood, Saqib
Abstract : Purpose: Organizations take a more oriented approach to the management of business processes since business processes are core elements of organizational performance. The purpose of this study is to bridge certain knowledge, theoretical, literature and contextual gaps that have not yet been addressed, in line with the organizational approach. The current study is also carried out in order to satisfy the needs of the industry for sustainable development that lead to economic prosperity in the country. Design/methodology/approach: Positivism research philosophy was espoused followed through a deductive approach. A structured questionnaire was used in order to collect the data from the employees working in public-sector organizations with a purposive sampling technique. In total, 364 respondents' data were analyzed by using Analysis of a Moment Structures guidelines and tested the sequential path accordingly. Findings: The results suggested that authentic leadership through sequential mediation of relational identification and positive emotions had a significant impact on employee engagement. Overall, three hypotheses were formulated on the basis of literature, and all hypotheses were supported. Research limitations/implications: The first significant limitation is the use of a single source of information. All variables (authentic leadership, employee engagement, gratitude, happiness and compassion and relational identification) were asked to be reported to individuals. In addition, the current study took only three positive emotions (gratitude, happiness and compassion). There are, however, a number of other emotions that can be taken to identify the relationship between authentic leadership and employee attitude. Originality/value: The plethora of research seeks to identify mechanisms that can overcome the challenge of employee engagement in the organizational sphere. To this end, organizations are continually identifying and implementing strategies to enhance employee engagement. Recently, the adoption of a bottom-up approach identified as a potential contributor to increasing employee engagement. It has also meant that authentic leadership is the best source of support for a bottom-up approach. However, limited research has been identified in relation to authentic leadership and positive employee emotions.